2010
DOI: 10.1038/ijo.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional regulation of interleukin-6 release from adipocytes

Abstract: Background and aims: As interleukin-6 (IL-6) has an important role in general metabolism with high circulating levels in obesity and other associated diseases, the factors regulating its synthesis and release have been considered possible therapeutic targets and have recently been studied. We examined the influence of three different diets, each having a different fatty acid compositionFsaturated, monounsaturated or polyunsaturated (coconut oil, olive oil and sunflower oil diets), on IL-6 release from rat adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Similarly, macrophages treated with EPA or DHA showed a decrease in LPS stimulated IL-6 mRNA and IL-6 production. In agreement with these findings, rats fed a diet high in n -6 PUFA-rich sunflower oil showed moderate IL-6 release from adipocytes, which was less than when fed a SFA-rich diet, but greater than when fed a MUFA-rich diet [79]. In addition, in mice fed a low fat diet or one of two high-fat diets, consisting of either unsaturated soybean oil or saturated palmitic acid for 16 weeks, MCP-1 expression in AT tissue increased for both high-fat diets compared to the low-fat diet.…”
Section: Interleukin-6supporting
confidence: 60%
“…Similarly, macrophages treated with EPA or DHA showed a decrease in LPS stimulated IL-6 mRNA and IL-6 production. In agreement with these findings, rats fed a diet high in n -6 PUFA-rich sunflower oil showed moderate IL-6 release from adipocytes, which was less than when fed a SFA-rich diet, but greater than when fed a MUFA-rich diet [79]. In addition, in mice fed a low fat diet or one of two high-fat diets, consisting of either unsaturated soybean oil or saturated palmitic acid for 16 weeks, MCP-1 expression in AT tissue increased for both high-fat diets compared to the low-fat diet.…”
Section: Interleukin-6supporting
confidence: 60%
“…Previous studies reported that the type of dietary lipid may influence plasma IL-6 levels [11,12] and IL-6 secretion from adipocytes [13]. In our study in exhausted mice, the levels were similar in the three diet groups, although sedentary mice fed safflower oil tended to have non-significant increases in plasma IL-6 levels compared with those fed lard.…”
Section: Discussioncontrasting
confidence: 29%
“…Other studies suggest that dietary n–6 PUFAs (safflower oil and corn oil) may increase plasma IL-6 levels compared to dietary fish oil [11,12]. Furthermore, different types of dietary lipids have varying effects on the regulation of IL-6 secretion from adipocytes [13]. Several studies have reported that IL-6 is associated with improved endurance performance in humans [14,15,16], suggesting a possible role for IL-6 in the biochemical pathways that determine endurance.…”
Section: Introductionmentioning
confidence: 99%
“…High content of monounsaturated fatty acids improves insulin sensitivity, provided the total amount of fat is below 38% [20]. Indeed monounsaturated fatty acids (olive oil) generate much less inflammatory factors than short chain fatty acids (coconut oil) or polyunsaturated fatty acids ( sun flower oil) [21]. High fat leads to adiposity if fat is saturated [22].…”
Section: Fat: From Theory To Practicementioning
confidence: 99%